Surface Modification with Phosphate and Hydroxyapatite of Porous Magnesium Scaffolds Fabricated by Binder Jet Additive Manufacturing - Kai Xiang Kuah; Mojtaba Salehi; Zihan Huang; Su Xia Zhang; Hang Li Seet; Mui Ling Sharon Nai; Daniel John Blackwood (Crystals, 2022)
The presence of porosity within magnesium-based orthopaedic implants is known to be beneficial, promoting cell proliferation and vascularisation. However, the presence of porosity increases the surface area available for corrosion, compounding the issue of high corrosion rates which has long been plaguing magnesium-based materials. This work looks at the influence of hydroxyapatite and phosphate conversion coatings on the corrosion performance of conventionally cast, dense Mg-Zn-Zr alloys and binder jet additive manufactured porous Mg-Zn-Zr scaffolds. The performance of coating on dense Mg-Zn-Zr was found to be more effective than the coating on the porous Mg-Zn-Zr scaffold, with the discrepancies attributed to both the microstructure and geometric influence of the binder jet additive manufactured, porous Mg-Zn-Zr scaffold, which not only increases the rate of hydrogen evolution but also reduces the ability of the hydrogen gas generated within the pore channels to escape to the sample’s surface. This restricts the effectiveness of coating application for porous Mg scaffold. Furthermore, the limited diffusion within the pore channels can also result in differing localized corrosion environments, causing discrepancies between the localised corrosion environment within the pore channels and that at the bulk electrolyte.